The specialized profiles for aircraft designed with “flying wing” scheme - Іщенко, С.О.; Лемко, О.Л. (Proceedings of National Aviation University, 2004)
There results of quantitative researches are considered, that were accomplished for high-lifting profiles with positive values of along moment and zero-values lifting force development. That profiles intended for aircrafts with “flying wing” scheme.